Some fishing methods in Balayan Bay. - Martinez, Rustico B. (College of Fisheries, University of the Philippines, 1954)
In view of the economic program being waged by our government for the rehabilitation and development of the fishing industry, and in the conservation and development of the fishing resources, this report is accomplished to evaluate the "bansig" fishing methods of fish capture which are now being employed by our fishermen. Knowledge of this gear is of great value to Filipino fishermen as a means of eradicating the destructive and illegal fishing grounds of the islands. This report does not only discuss the method of operation but also the suitable fishing areas by which this type of gear can be improved and modernized, and at the same time conserved our fish products in order to assure a constant supply of the commodity from year to year. This paper covers my observation on the operation of the "bansigan" while serving as an apprentice student on board the "M/B Queen Mary", a "bansigan" operated in almost all the municipal waters of Batangas Province, particularly balayan Bay and in some waters of oriental Mindoro. Some minor fishing gear or methods used in the balayan bay are discussed in this final report. Roundhaul seine, multiple handline, gill net and beach seines are some of the many kinds used in the said bay.